DEVELOPMENT OF HUMAN RESOURCE MANAGEMENT SYSTEM TO BECOME A HIGH-PERFORMANCE ORGANIZATION IN ACCORDANCE WITH GOOD GOVERNANCE PRINCIPLES - Kosit, Sutee; Anusonphat, Nalaumon (Journal of MCU Nakhondhat, 2024)
A study of the This research on the Development of Human Resource Management System towards a High Performance Organization Based on Good Governance has the following objectives: 1) The study the human resource management system towards a high performance organization based on good governance; 2) The compare the human resource management systems towards a high performance organization based on good governance; and 3) To study the approach to developing the human resource management system towards a high performance organization based on good governance. This research is a quantitative research. The sample used in the research is the people in Phra Nakhon Si Ayutthaya Municipality by purposive selection, totaling 100 people. The research instrument is a questionnaire. The statistical analysis is done by finding the mean, frequency, percentage, standard deviation, and testing the hypothesis with t-value and F-value. The research results found that 1) The overall human resource management system for high-performance organizations based on good governance was at a high level in each aspect; 2) The results of the comparison of human resource management systems for high-performance organizations based on good governance classified by gender and age were different in all aspects; and 3) The results of the research on the development of human resource management systems for high-performance organizations based on good governance found that 1) In terms of manpower management, the government sector should prepare a workforce plan by analyzing, planning policies, and preparing manpower data; 2) In terms of system and innovation development, the government sector should develop systems and innovations, based on local wisdom; and 3) In terms of digital technology development, the government sector should develop a digital technology infrastructure system that is modern and widely distributed.